P024: Physician reporting of medically unfit drivers: knowledge, attitudes, and practice. (15th May 2017) - Brubacher, J.R.; Renschler, C.; Huang, B.; Lee, W.C.; Gomez, A.M.; Chan, H.; Erdelyi, S.; Purssell, R.
Abstract : Introduction: Medical conditions that impair perception, cognition or motor skills may make people unfit to drive. Reporting unfit drivers to licensing authorities is seen by many as a public health obligation. This study investigates physician knowledge, attitudes and practice around the management of medically unfit drivers.Methods: We used an online survey to explore physician knowledge of fitness to drive issues and their attitudes and practice with regard to counselling and reporting unfit drivers. Email invitations to participate in the survey were sent to all physicians in BC through DoctorsofBC and to all emergency physicians (EPs) in the UBC Department of Emergency Medicine.Results: We received responses from 242 physicians (47% EPs, 40% GPs, 13% others). The majority (78%) reported little/no knowledge on determining driver fitness and 94% had little/no training around guidelines, reporting, and laws involving fitness to drive. Most (88%) agreed that physicians should be obligated to advise medically unfit patients not to drive, and 74% reported that they often warn patients not to drive. The majority of physicians also chart their opinion of patients' fitness to drive (67% do so more than twice per year). Most respondents (70%) indicated that it is "always appropriate" to report definitely unfit drivers whereas only 25% indicated that it is "always appropriate" to report potentially unfit drivers. However, in practice physicians see far more unfit drivers than they report to licensing authority: 67% of physicians encounter definitely unfit drivers more than twice per year but only 19% report definitely unfit drivers more than twice per year and 34% never report definitely unfit drivers. Compared to other physicians, EPs reported less knowledge and training about criteria for determining fitness to drive, were more likely to feel that reporting unfit drivers was not their responsibility, and were less likely to report unfit drivers to licensing authorities.Conclusion: Our findings indicate a need for more education and information resources to help physicians, particularly EPs, identify and manage medically unfit drivers. Although most physicians warn unfit drivers not to drive and document this in medical records, many medically unfit drivers are not reported to licensing authorities, a potential public health problem that should be further investigated.